Air pollution exposure and pregnancy outcomes among women with polycystic ovary syndrome - Zhu, Qianqian; Cai, Jing; Guo, Haiyan; Zhao, Yan; Lin, Jiaying (Frontiers in Public Health, 2022)
Background: The relationship of air pollution with reproductive outcomes has become present research focus. However, there is lack of research on the relationship of air pollution with PCOS. Methods: A retrospective cohort study included a total of 1652 PCOS women and 12543 non- PCOS women from January 1, 2013, to December 31, 2019. The daily average concentration data of six air pollutants (PM2.5, PM10, O3, NO2, SO2, and CO) during different exposure windows was obtained. Generalized estimating equation models were performed to evaluate the association of air pollution with pregnancy outcomes. Results: Air pollutants were not found to have a significant association with pregnancy rate among PCOS patients. However, each IQR increase of PM10 exposure during period 3 (embryo transfer to serum HCG test) was associated with the reduced clinical pregnancy rate (adjusted OR=0.92,95%CI:0.84-0.99) for non-PCOS patients. Patients without PCOS showed lower clinical pregnancy rate with increased exposure to NO2 during period 2 (oocyte retrieval to embryo transfer) and period 5 (start of gonadotropin medication to embryo transfer) with aORs and 95%CIs of 0.94(0.88,0.99) and 0.94(0.88, 0.98), respectively. Each IQR increment of SO2 among non-PCOS patients during period 1 (start of gonadotropin medication to oocyte retrieval), period 2, period 5, and period 6 (start of gonadotropin medication to serum HCG test) was related with a decreased clinical pregnancy rate. For live birth rate, no significant relationship was found between air pollutants including PM2.5, PM10, SO2, NO2, CO and O3 and live birth rate for PCOS women. However, women without PCOS presented lower probability of live birth with exposure of SO2 during period 1, period 2, period 5, and period 6. Conclusions: This retrospective study of reproductive-aged women observed no significant relationships between ambient pollutants and pregnancy outcomes among women with PCOS, but negative associations among women without PCOS.